Blockchain in Voting System Application - Sakinah Burhanuddin, Nur; Hafizhelmi Kamaru Zaman, Fadhlan; Ihsan Mohd Yassin, Ahmad; Md Tahir, Nooritawati (International Journal of Engineering and Technology, 2018)
Two of the most familiar method of voting is through voting polls and online voting. The main problem with conventional method is the insecurity of the votes to be untemper. Another problem of voting methods is the existence of fraud in voting system. This paper is to propose a method in overcoming these flaws and problems by using the Blockchain technology. Blockchain technology is a secured database and has very high security. The technical concept of the Blockchain technology has many advantages and benefits that could be applied to many technical sectors and have the possibility in changing the world. The concept for this project is to develop a cryptocurrency implementation in the voting system. From there, the transaction votes are kept in the blockchain could be illustrated by examining the block hashes. The outcome of the project shows a transaction of coins from one voterâ€™s wallet into two candidatesâ€™ wallet. The transactions were approved through a process of mining and the transactions of coins were a success. The data of the transactions were kept in the blockchain where unique blockhash, which acted as the blockâ€™s fingerprint were generated. From there, the integrity of the blockchain technology is illustrated.Â Â